Influence of hygrothermal conditioning on the properties of compressed kenaf fiber / epoxy reinforced aluminium laminates - Edynoor Osman; Mohd Warikh Abd. Rashid; Mohd Edeerozey Abd Manaf; Toshihiro Moriga; Hazlinda Kamarudin (Journal of Mechanical Engineering and Sciences, 2020)
Increasing environmental concerns have encouraged researchers to utilize natural fibers in the development process for various applications of polymer composites. Hydrophilic nature and low strength of natural fiber become a significant issue and need improvement forwide structural application. Therefore, fiber metal laminates (FML) are selected for overcoming the disadvantages of natural fiber composites with their outstanding degradation resistance. This study has been carried out to evaluate water and temperature effect also known as hygrothermal effect onto kenaf fiber reinforced aluminium laminates (KeRALL) and kenaf fiber reinforced composite (KFRC) as compared to pristine sample. Samples were fabricated by warm compression method and immersed at 30°C, 60°C and 80°C in water bath for 5 days. KeRALL at temperature 30°C, showed the lowest water absorption rate compared to temperature 60°C and 80°C. Both KeRALL and KFRC, at temperature 80 °C showed the fastest water absorption and the earliest to reach saturation state, followed by temperature of 60°C and 30°C. Flexural and impact properties shows the decremented trends at temperature of 30°C, 60°C and 80°C. Interlaminar shear stress (ILSS) show a decrement by 7 % at 30°C, followed by 66 % at 60°C and 54 % at 80°C. Dynamic mechanical analysis (DMA) shows storage and loss modulus of KeRALL were decreased as temperature increased. The decrement is associated with fiber pull out, crack propagation, matrix fracture and delamination as the result of the hygrothermal influence as manifested by the fractographic images. It can be concluded that hygrothermal gives the significant effect on the properties of KeRALL. The finding suggests that KeRALL has high potential as a new sustainable FML composite and can be considered as apromising candidate for future structural applications.